Pengaruh Audit Internal Dan Sistem Informasi Akuntansi Terhadap Kecurangan Akuntansi Pada PT Pegadaian (Persero) Cabang Ngupasan - Sebayang, Laura Sindhea; Budiantara, Martinus (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of internal audit and accounting information systems on accounting fraud at PT Pegadaian (Persero) Ngupasan Branch. Effective internal audits and accounting information systems are expected to be able to identify potential fraud and strengthen internal controls. This research technique is quantitative with a data acquisition method using a questionnaire distributed to employees who play a role in internal audit and management of accounting information systems. The results of this research indicate that internal audit and accounting information systems at PT Pegadaian (Persero) Ngupasan Branch do not have a significant effect on accounting fraud. This indicates that other factors outside internal audit and accounting information systems may contribute more to influencing accounting fraud, and further research is needed to identify these factors.